THE PHENOMENON OF CHEATING AMONG ELEMENTARY SCHOOL STUDENTS - Daviq Chairilsyah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Cheating on Elementary School Students has occurred for a long time but it is still hard for teachers and the schools to overcome this phenomenon. Cheating will cause the children to be dishonest in achieving a high score. Besides, cheating will also be impactful until the students become adults. This behavior is harmful to other students who have studied hard and been honest in completing exams and assignments from teachers at school. Cheating is an act that is dishonest, fraudulent, and justifies anything to get a high score in completing the task, especially on tests or exams. This article applied a literature review as the research methodology to explain the situational, dispositional, personal, and external factors causing cheating. It was observed that cheating mostly acted by students were changing the answers in the exam after reading notes when the teacher was out of the classroom, using the notes prepared for answering the questions, looking at or asking for answers from other students, and allowing other students to view or copy his answers. This article encouraged the participation from parents, classroom teachers, and school institutions to work together to improve the students’ self-awareness in order that cheating would not become a habit to reach a high score in the future.